2016
DOI: 10.1371/journal.pone.0157082
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Polyphenols Interact with Staphylococcal Enterotoxin A and Inhibit Toxin Activity

Abstract: This study was performed to investigate the inhibitory effects of 16 different plant-derived polyphenols on the toxicity of staphylococcal enterotoxin A (SEA). Plant-derived polyphenols were incubated with the cultured Staphylococcus aureus C-29 to investigate the effects of these samples on SEA produced from C-29 using Western blot analysis. Twelve polyphenols (0.1–0.5 mg/mL) inhibited the interaction between the anti-SEA antibody and SEA. We examined whether the polyphenols could directly interact with SEA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The polyphenol that interacts strongly with the protein is small enough to pass through the protein molecules and must be large enough to crosslink the peptide chains [ 13 ]. Additionally, in our previous study, the molecular weight of the polyphenols that weakly interacted was more than 1000, whereas the molecular weight of the polyphenols that strongly interacted was 1000 or less [ 14 ]. In the dimer to tetramer group, it was suggested that the interaction was weak when the molecular weight of polyphenol was less than or equal to 1000.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polyphenol that interacts strongly with the protein is small enough to pass through the protein molecules and must be large enough to crosslink the peptide chains [ 13 ]. Additionally, in our previous study, the molecular weight of the polyphenols that weakly interacted was more than 1000, whereas the molecular weight of the polyphenols that strongly interacted was 1000 or less [ 14 ]. In the dimer to tetramer group, it was suggested that the interaction was weak when the molecular weight of polyphenol was less than or equal to 1000.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction affinities of AP with SEA toxin active sites (emetic and superantigenic activities) were analyzed using four different synthetic peptides and rabbit antibodies with their corresponding peptides (A-2, 21–40; A-3, 35–50; A-6, 81–100; or A-10, 161–180) [ 15 ]. Amino acid residues 21–50 and 81–100 of SEA molecule are necessary to superantigenic and emetic activities in house musk shrews [ 14 ]. Treatment with AP resulted in a dose-dependent interaction of SEA active sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Punicalagin can chelate iron and can interfere with antibody binding to the S. aureus enterotoxin, but its biochemical mechanistic action on microbial proteins is unknown. Aspiring to understand the mechanistic action of punicalagin on S. aureus , we performed a quantitative, comparative analysis of the proteome of S. aureus exposed to punicalagin.…”
Section: Introductionmentioning
confidence: 99%